Growth and Yield of Two Tomato Plant Varieties in Dryland Areas with Agronomic Modification Treatments - Baiq Eliza Prizma Mahardhika; I Komang Damar Jaya; Sudirman; I Gede Putu Wirarama Wedashwara Wirawan; Bambang Budi Santoso (Jurnal Penelitian Pendidikan IPA, 2024)
The yield of tomato plants in dryland areas has been suboptimal due to environmental constraints such as poor soil health and high sunlight intensity. Appropriate agronomic modifications are necessary to improve crop yields while maintaining soil health. This study investigated the impact of various agronomic modification treatments on the growth and yield of tomato plants in dryland regions. The experiment was conducted in Gumantar Village, North Lombok Regency, during the dry season from June to August 2023. The agronomic modifications included a seaweed biochar treatment at a rate of 10 tons per hectare and 45% shading, with a control group that had no modifications. Three treatments were tested on two varieties of tomato plants: hybrid and local superior. The treatments were organized with four replications in a randomized complete block design with split plots, where agronomic modifications served as the main plots and the tomato varieties as the subplots. The results indicated that the interaction of agronomic modifications and plant varieties impacted the growth of tomato plants and various environmental factors. The hybrid variety under shading treatment exhibited the best growth. Additionally, this hybrid variety produced 59.6% more fruit than the local superior variety, yielding an average of 66 fruits and weighing 3.00 kg per plant. This study suggests that incorporating agronomic modifications, such as biochar treatment and selecting the appropriate variety, can enhance tomato yields in dryland areas.